PERTUMBUHAN DAN HASIL SELADA PADA BERBAGAI KERAPATAN JAGUNG DALAM POLA TUMPANG SARI - Zulkarnain, Zulkarnain (Jurnal Ilmu-Ilmu Pertanian, 2005)
This study was aimed at investigating the effect of various maize density on the growth and yield of lettuce in a multiple cropping system. The study was carried out on February through to April 2004 at the Experimental Farm, Agricultural Faculty (University of Jambi, Mendalo Darat Campus, located at approximately 35 m above sea level and Ultisol soil group. The culture technique followed the routine organic farming system with no use of inorganic fertilizers nor pesticides. Manure of chicken waste was used as a base fertilizer at the rate of 20 ton ha''. Lettuce cv. Grand Rapid were planted at 70 x 25 density in the between of the rows of maize cv. Arjuna that were planted at 70 x 80 cm, 70 x 60 cm, 70 x 40 cm and 70 x 20 cm density. One treatment with no maize was used ss the control. The results indicated that maize planting at density of 70 x 60 cm produce the best growth and yield performance on lettuce as well as maize itself, Though the monoculture system (with no maize) or multiple cropping at 70 x 80 cm density produced higher lettuce fresh weight than those planted at 70 x 60 density, the difference was not significant. Maize density of wider or narrower than 70 x 60 cm were liable to produce lower yield, in the form of stalk number.